Heritability coefficients of growth traits of rainbow trout from a national selection programme - V. Golubović; M. Stanković; D. Vukojević; D. Stanojević; R. Djedović; S. Marić; Z. Marković (South African Journal of Animal Science)
In order to create a selection programme aimed at improving the production characteristics of rainbow trout, broodstocks from eight fish farms in the Republic of Serbia were collected in 2010. The spawning of broodstocks, hatching of eggs, and rearing of offspring from different families of known parentage, until marking at five months of age, were carried out in individual tanks under strictly controlled conditions. After tagging, the fish were reared in a flow-through system on a commercial fish farm, where their growth was further monitored. The study of the phenotypic variability and heritability coefficients of the broodstock was carried out on a sample of 6565 individuals. The body weights and total lengths of the individuals were measured at five, 12, 24, and 36 months of age. Factors such as the year of spawning and sex proved to be highly statistically significant for the observed growth traits, while the heritability values of the analysed traits were moderate to high (0.22–0.68). The estimated heritability values provide an excellent basis for the continuation of the selective breeding programme, which will ultimately lead to the improvement of salmonid aquaculture and the profitability of rainbow trout production in the Republic of Serbia.